# Trapezoidal Footing Formula with Calculation

2 min readOct 18, 2019

--

# Trapezoidal Footing Formula

As shown in Fig of trapezoidal footing. In this footing, two different parts show in fig.

**Rectangle/ Square Cubic Area****Truncated Pyramid Area**

**Trapezoidal Footing =**

**Rectangle/ Squared Cubic Area (V1)**

**Truncated Pyramid Area (V2)**

**The volume of trapezoidal footing**

= Rectangle/ Square cubic area (V1) + Truncated Pyramid Area (V2)

**V = V1 +V2**

## V = Volume of Trapzodial Footing .

## V1 = Rectangle/ Square Cubic Area (V1)

**Rectangle ****Cubic Area**

**V1 = L x B x H**- L = Length of the cuboid = m. / mm
**.** - B = Breadth of the cuboid = m. / mm
**.** - H = Hight of the cuboid = m. / mm
**.**

## V2 = Truncated Pyramid Area (V2)

**Truncated Pyramid Area (V2)**

**V2 = (h/3) (A1 + A2 +√(A1 . A2))****A1 = L1 x B1 = Sq.m /Sq. mm**- A1 = Truncated Pyramid Bottom Area
**A1 = L2 x B2 = Sq.m /Sq. mm**- A2 = Truncated Pyramid Top Area
- h = Height of Truncated Pyramid = M. / MM
**.**

# Derive Trapezoidal Pyramid Formula.

**V2 = (h/3) (A1 + A2 +√(A1 + A2))**

**One Cubicl = Six part of Truncated Pyramid**

- V2 =
**Truncated Pyramid Area** **Cubic**= 1/6 Truncated Pyramid area- A3 =1/6 Truncated Pyramid Area

**Truncated PyramidArea**

**= 1/6 A3**

= **1/6 (a-b) 3**

**= 1/6 (a-b) (a2 + b2 +ab )**

**a-b = 2h**

**a2 = a x a = A1**

**b2 = b x b = A2**